ESG COMPETENCES AND SKILLS IN LIFELONG EDUCATION FOR SUSTAINABILITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Sustainability paradigm being a global trend nowadays embraces not only a shift in problematics numerous areas of knowledge, but primarily a leap in mindset, which involves a revision of values and priorities for humanity at all. Thus, education for sustainable development and acquiring ESG (Environmental, Social, Governance) competences start to be a relevant drift in learning space. This area becoming a targeting for international regulation and an extensive part of educational services in response to labour market demands. This paper is focused on analysis of current state and prospectives of ESG education in EU. Based on the assessment of existing frameworks and stakeholders’ needs an ESG-competences map was proposed. In this research a qualitative approach was applied. Thus, mostly secondary sources of information were used, particularly similar-topic scholars’ studies, databases, ESG and education regulatory documents and analytics, open access information from internet resources. Logical and comparative analysis was used for data processing. It was assessed educational models applying, content and institutional forms of existing ESG-programs, in higher education, specialists’ upskilling, and livelong education as well. There were considered main programs offered in education for sustainability and top ESG-skills required as far. Existing problems in education for sustainability were identified and a set of recommendations to develop lifelong acquiring ESG-knowledge system was provided.